Harvard Business Review on Strategic Renewal (Harvard Business Review Paperback Series) - Harvard Business School Publishing Corporation (Harvard Business Press, 2008)
Technologies, consumer preferences, and market dynamics are changing faster than ever. To help your company stay competitive in the face of accelerating change, you need to continually test and redefine your strategy. But strategic renewal isn't easy.